19 MULTIPLE SITES OF CARDIAC RUPTURE IN THE SETTING OF ACUTE MYOCARDIAL INFARCTION WITH NON-OBSTRUCTIVE CORONARY ARTERY DISEASE. (1st January 2005) - Mehrle, A. P.; Winniford, M. D.; McMullan, M. R.; Skelton, T. N.
Abstract : Cardiac rupture is a rare but devastating complication of myocardial infarction. Free wall rupture, papillary muscle rupture and ventricular septal defect have been described extensively in the literature. Rupture most often occurs in patients with occlusion of a single vessel or severe multivessel coronary artery disease. We describe an unusual case of a 66 year old man who presented to our institution with chest pain of 12 hours duration and ST-segment elevation in leads V4-V6 and II, III and AVF. Echocardiogram revealed an apical ventricular septal defect by Doppler and normal systolic function with apical akinesis. A small pericardial effusion was found as well. Coronary angiography revealed minor luminal irregularities and TIMI 3 flow in all vessels. The right ventricle filled extensively with contrast during left ventriculography. During surgery, the entire free wall of the left ventricle was found to be infarcted. A 2 × 2 mm rupture existed between two large marginal branches. Ventricular septal defects measuring 3 × 3 mm at the apex and mid ventricle were found. The areas of rupture could not be closed due to the extent of surrounding hemorrhage and necrosis. Rupture of the ventricular septum or free wall usually occurs 2 to 4 days after a large infarction and is more common in patients without prior infarction or hypertrophy. Rupture of the anteroapical ventricular septum usually occurs after left anterior descending (LAD) occlusion while rupture of the lateral free wall between obtuse marginal branches occurs after occlusion of the left circumflex or large, dominant right coronary artery. The most remarkable features of this case are (1) near simultaneous rupture in two different vascular territories, (2) absence of angiographically significant coronary disease, (3) early appearance of rupture, within 12 hours of symptom onset, and (4) absence of extensive wall motion abnormality by echocardiography or angiography in the areas of rupture. Possible etiologies of this unusual event include (a) transient occlusion of left main or both the LAD and circumflex arteries due to thrombosis or spasm with reperfusion causing hemorrhage or (b) severe diffuse microvascular obstruction due to thromboemboli or vasospasm.